Hazard Identification, Risk Assessment, Risk Control (HIRARC) For Grinding Operation At The Oil And Gas Company Topside Project - Putriana Helmi; Mohd Akhir Ahmad; Muhamad Zulhilmi Bin Md Foa'at (Progress in Engineering Application and Technology, 2026)
Grinding operations are wide applied in the construction and fabrication works, particularly in oil and gas topside projects, but they pose significant occupational safety and health risks if not properly controlled. This study aims to identify hazards, assess associated risk levels, and propose appropriate control measures for grinding operations using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach. The study was conducted at an oil and gas company topside project located at Malaysia Marine and Heavy Engineering (MMHE). A mixed-method research design was adopted, involving HIRARC assessment, structured questionnaires and semi- structured interviews with Health, Safety and Environment (HSE) personnel and foreman. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed thematically in accordance with the DOSH HIRARC Guideline 2008. The findings identified various physical, mechanical, electrical and environmental hazards , including grinder kickback, flying metal particles, defective grinding disc, excessive noise, hand-arm vibration, electrical shock and poor housekeeping. Several hazards were classified as medium to high risk, particularly during equipment preparation and active grinding activities. Although existing congrol measures such as personal protective equipment, training, and supervision were implemented, unsafe work practices and human factors were still observed. The findings indicate that systematic HIRARC implementation can support safer grinding operations and reduce the likelihood of work related injuries in industrial projects